Stakeholder Perspectives on Using and Developing the MYPLAN Suicide Prevention Mobile Phone Application: A Focus Group Study. Issue 1 (2nd January 2020) - Buus, Niels; Erlangsen, Annette; River, Jo; Andreasson, Kate; Frandsen, Hanne; Larsen, Jette Louise Skovgaard; Nordentoft, Merete; Juel, Anette
Abstract : The objective of this study was to explore different stakeholder perspectives on the MYPLAN app for suicide prevention safety planning. The study was a comparative analysis of 4 focus groups with Danish MYPLAN stakeholders, young users, adult users, relatives, and clinicians. The focus groups were audio recorded, transcribed, and subjected to a thematic analysis. The analysis contextualized the participants' experiences of the benefits and limitations of MYPLAN. While participants believed that MYPLAN could potentially interrupt early stages of a suicidal process, clinicians' involvement in safety planning was considered important. MYPLAN could potentially give users a sense of increased personal control but learning how to effectively safety plan was not perceived to be simple and additional support should be considered for MYPLAN users.